Microtubule Motility Powered by Dual Motor Protein System and Their Electrical Docking - Kamisetty1, N.K.; Ikuta1, J.; Kotera1, H.; Yokokawa1, R. (Asian Journal of Chemistry, 2013)
A flow chamber was assembled from Au-coated (top) and indium tin oxide (ITO)-coated (bottom) glass coverslips using a double sided tape and subsequently modified with dynein and kinesin motor proteins respectively. Microtubule motility with respect to their polarity was observed on both top and bottom surface. On the other hand, electrical docking of microtubules by applying a pulse voltage between the Au and ITO electrodes of the chamber was also performed. The microtubule density was enhanced in comparison to the control on the electrode surface from the bulk solution. These studies would be useful in fabricating micro/nano fluidic systems in which the motility of microtubules could be controlled in more than one direction.